Characterization of Lactobacillus rhamnosus MP01 and Lactobacillus plantarum MP02 and Assessment of Their Potential for the Prevention of Gastrointestinal Infections in an Experimental Canine Model - Fernández, Leónides; Martínez, Raquel; Pérez, Manuela; Arroyo, Rebeca; Rodríguez, Juan M. (Frontiers in Microbiology, 2019)
The aim of the present study was to evaluate the probiotic potential of Lactobacillus rhamnosus MP01 and Lactobacillus plantarum MP02, two strains isolated from canine milk. These two isolates were characterized in vitro for their survival to conditions similar to those found in the canine gastrointestinal tract, production of antimicrobial compounds, adherence to intestinal mucin, degradation of mucin, and antibiotic sensitivity. Globally, both strains exhibited a high in vitro probiotic potential. Finally, their potential for the prevention of gastrointestinal infections was evaluated in an experimental canine model using 1-month-old puppies. A group of 12 German shepherd puppies, 6 males and 6 females, received L. rhamnosus MP01 daily for 2 months and a second group of 12 puppies, 6 males and 6 females, of the same breed received L. plantarum MP02 during the same period of time. The same experimental approach was carried with Yorkshire puppies. Additionally, the trial included 12 dogs of each breed in the placebo groups. The results demonstrated that administration of the strains resulted in a significant preventive effect of gastrointestinal infections in such populations.